2023
DOI: 10.1007/s12079-023-00792-5
|View full text |Cite
|
Sign up to set email alerts
|

GPR56 signaling pathway network and its dynamics in the mesenchymal transition of glioblastoma

Raksha A. Ganesh,
Krishnan Venkataraman,
Ravi Sirdeshmukh

Abstract: G protein-coupled receptor 56 (GPR56/ADGRG1) is a multifunctional adhesion GPCR involved in diverse biological processes ranging from development to cancer. In our earlier study, we reported that GPR56 is expressed heterogeneously in glioblastoma (GBM) and is involved in the mesenchymal transition, making it a promising therapeutic target (Ganesh et al., 2022). Despite its important role in cancer, its mechanism of action or signaling is not completely understood. Thus, based on transcriptomic, proteomic, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…In line with these observations, pathways commonly activated in various human PBTs and promoting invasiveness and the expression of pro-inflammatory molecules [20] involved in the regulation of TME infiltrates are those mediated by 5-Lipoxygenases (5-LOX) [21,22], COX-2 and cytokines [23,24] with oncogenic properties [18]. Interestingly, a multifunctional enzyme, the transglutaminase 2 (TG2) might have a role in the inflammatory processes, through NF-κB upregulation and, mesenchymal transition promotion in GBM [25,26]. In this context, previous research showed an increased CD4 + and CD8 + T cell and natural killer (NK) cell infiltration in the TME of lower grade gliomas (LGGs), and conversely a sparse infiltration in immunosuppressed high-grade gliomas (HGGs) [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…In line with these observations, pathways commonly activated in various human PBTs and promoting invasiveness and the expression of pro-inflammatory molecules [20] involved in the regulation of TME infiltrates are those mediated by 5-Lipoxygenases (5-LOX) [21,22], COX-2 and cytokines [23,24] with oncogenic properties [18]. Interestingly, a multifunctional enzyme, the transglutaminase 2 (TG2) might have a role in the inflammatory processes, through NF-κB upregulation and, mesenchymal transition promotion in GBM [25,26]. In this context, previous research showed an increased CD4 + and CD8 + T cell and natural killer (NK) cell infiltration in the TME of lower grade gliomas (LGGs), and conversely a sparse infiltration in immunosuppressed high-grade gliomas (HGGs) [27][28][29].…”
Section: Introductionmentioning
confidence: 99%